Status of awareness and action of student’s HCMC University of Technology and Education for “climate change” now - Nguyễn Thị Như Thúy; Đặng Thị Minh Tuấn (Journal of Technical Education Science, 2019)
This paper presents an overview of current climate change issues from concept to expression and its causes. At the same time, this paper understands the current state of awareness and action to respond to climate change of students at the Ho Chi Minh City University of Technology and Education and judge the effectiveness of these coping actions. From there, some solutions to raise awareness of students of the Ho Chi Minh City University of Technology and Educationon on climate change and promote further the effectiveness of actions to respond to climate change in students, contributes to the protection of the living environment, towards holistic and harmonious development.